Pelatihan Pembuatan Interactive Media bagi Guru Sekolah Dasar Negeri Sawahan Kecamatan Turen Kabupaten Malang - Teguh Sulistyo; Nara Sari; Agus Sholeh (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
The online teaching-learning process mainly means the absence of physical interaction between teachers and students. In this context, the existence of the Web. 2.0-based technologies is expected to bridge the distance between teacher-student and student-student communication. Somehow, it will be a big problem if the teachers do not administer online learning well and appropriately. The facts show that online learning still faces some obstacles, such as the quality of the Internet connection and teacher-student and student-student interaction, including the media applied in the teaching-learning process. Thus, the present community service that involved 30 teachers of elementary schools aims at empowering the teachers with the ability to create interactive media. This activity covers briefing, lecture, demonstration, and workshop on interactive media, such as PowerPoint Presentation (PPT) with voice, Kahoot, and Padlet. The results demonstrate that teachers believe that interactive online learning is not as complicated as they thought and applied in the classrooms.